UUV Autonomous Decision-Making Method Based on Dynamic Influence Diagram. (17th June 2020) - Yao, Hongfei; Wang, Hongjian; Wang, Ying
Abstract : Considering the complexity and uncertainty of decision-making in the operating environment of an unmanned underwater vehicle (UUV), this study proposes an autonomous decision-making method based on the dynamic influence diagram (DID) and expected utility theory. First, a threat assessment model is established for situation awareness of the UUV. Accordingly, a DID model is developed for autonomous decision-making of the UUV. Then, based on the threat assessment results for the UUV, the utility of each decision-making plan in the decision-making nodes is inferred and predicted. Subsequently, the principle of maximum expected utility is used to select an optimal autonomous decision-making plan. Finally, the effectiveness of the DID method is verified by simulation. Compared with the traditional expert systems, the DID system shows great adaptability and exhibits better solutions of dynamic decision problems under uncertainty.